Loss of oligodendrocyte ErbB receptor signaling leads to hypomyelination, reduced density of parvalbumin‐expressing interneurons, and inhibitory function in the auditory cortex. Issue 2 (2nd September 2022) - Borges, Beatriz C.; Meng, Xiangying; Long, Patrick; Kanold, Patrick O.; Corfas, Gabriel
Abstract: For a long time, myelin was thought to be restricted to excitatory neurons, and studies on dysmyelination focused primarily on excitatory cells. Recent evidence showed that axons of inhibitory neurons in the neocortex are also myelinated, but the role of myelin on inhibitory circuits remains unknown. Here we studied the impact of mild hypomyelination on both excitatory and inhibitory connectivity in the primary auditory cortex (A1) with well‐characterized mouse models of hypomyelination due to loss of oligodendrocyte ErbB receptor signaling. Using laser‐scanning photostimulation, we found that mice with mild hypomyelination have reduced functional inhibitory connections to A1 L2/3 neurons without changes in excitatory connections, resulting in altered excitatory/inhibitory balance. These effects are not associated with altered expression of GABAergic and glutamatergic synaptic components, but with reduced density of parvalbumin‐positive (PV + ) neurons, axons, and synaptic terminals, which reflect reduced PV expression by interneurons rather than PV + neuronal loss. While immunostaining shows that hypomyelination occurs in both PV + and PV − axons, there is a strong correlation between MBP and PV expression, suggesting that myelination influences PV expression. Together, the results indicate that mild hypomyelination impacts A1 neuronal networks, reducing inhibitory activity, and shifting networks towards excitation. Main Point: Loss of oligodendrocyte ErbB receptor signaling leads to A1 hypomyelination, reduced PV expression and density of PV + neurons and synapses, hypoconnectivity of inhibitory circuits and shift of the E/I balance towards excitation.